The washback of the abolition of the national examination in Indonesia - Auladi, Ifan Rikhza (Indonesian Journal of Education and Pedagogy, 2024)
The National Examination (NE) is abolished in 2021, marking the beginning of a new educational evaluation paradigm in Indonesia. The regulation considers some reasons: the suitability of the test, the development of teaching methods, and the enhancement of the quality of national education. Under the abolition of NE, the regulation constitutes the establishment of School-Based Assessment (SBA), conducted by the teachers in the forms of portfolios, assignments, tests, and/or other assessments following the regulation from each school. Therefore, the present research aims at investigating English teachers' perception towards the abolition of NE and the washback of the abolition of NE on the teaching plan of English language learning in the aspect of classroom instructional behaviours and the content of the curriculum. The sequential mixed-methods research (MMR) works with quantitative and qualitative data from 51 respondents in an online questionnaire and four teachers participated in a semi-structured interview. It was then found that the establishment of SBA replacing NE obtains positive responses from the teachers as it is perceived more reliable with objectives of the English curriculum, which attempts to elevate students' high order thinking skills. The abolition of NE triggers the teachers to vary their teaching methods and techniques by using more communicative approaches; however, the change in assessment does not influence teachers' domination in classroom activities and talking activity. The teachers highly emphasize the use of previous exam papers in the preparation of SBA. In addition, the teachers remain highly prioritizing students' success in SBA, which retains exam papers, as the level of students' language proficiency is relatively low. Referring to the findings, the related parties can measure the washback of the abolition of NE for further improvement in the language assessment.